People Believe and Behave as if Consumers of Natural Foods Are Especially Virtuous - Taylor, Zoe; Stevenson, Richard J. (Frontiers in Psychology, 2018)
We examined here whether people believe consumers of natural foods are more virtuous than consumers of unnatural foods. In Study One we asked student participants (n = 84; 77 female, M age = 19.5) to form an impression of another person based solely upon whether they ate natural or unnatural foods, these being determined in a pilot survey. On an open response format, participants reported more positive moral and health traits in consumers of natural foods. These findings were further confirmed using rating-based evaluations. In Study Two we determined if this belief in the virtuousness of natural food consumers translated into behaviour. Student participants (n = 40; 25 female, M age = 20.2) played a trust game, exchanging tokens with a fictitious player. Incidental diet information about the fictitious player was provided, with participants in one group playing against a natural food consumer and those in another against an unnatural food consumer. Participants who played against a natural food consumer behaved as if they trusted this person more, and their performance on the game was predicted by how moral they felt the fictitious player was, but not by other attributes such as health. These findings suggest that people believe consumers of natural food are more virtuous, and we suggest this is driven by the altruistic attitudes that people believe to be associated with natural food consumption.